2020
DOI: 10.1177/1059840519899439
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal of School Nurse Health Services and Programs in North Carolina Public Schools, 2006–2016

Abstract: School nurses are instrumental in delivering health services to children in schools. This study addresses the gap in school nurse health services data, examining patterns in health services and programs provided by school nurses between 2006 and 2016 for students in North Carolina public schools. This study focused on services and programs related to asthma and diabetes, two health conditions that affect millions of children in the United States. Over 1.46 million children attend North Carolina public schools.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Prior studies have reported that school staff, despite lacking a medical background, with proper training and oversight by the school nurse, can facilitate a safe environment for students and assist them with their diabetes care until a nurse is available onsite 24 . North Carolina school nurses offer a multitude of trainings for teachers and other school staff in the building 21 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have reported that school staff, despite lacking a medical background, with proper training and oversight by the school nurse, can facilitate a safe environment for students and assist them with their diabetes care until a nurse is available onsite 24 . North Carolina school nurses offer a multitude of trainings for teachers and other school staff in the building 21 …”
Section: Discussionmentioning
confidence: 99%
“…School nurses representing all 115 public school districts in NC reported data each school year. These data represent 1.46 million students enrolled in public elementary (K‐5th grades), middle (6th‐8th grades), and high (9th‐12th grades) schools 21 . The sample included five school years (2011/2012 through 2015/2016) for which there were complete data on nursing interventions and student outcomes for asthma and diabetes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…School nurses should be able to respond appropriately to a variety of health needs of students and staff in schools. Asthma, attention deficit hyperactivity disorder, and severe allergies were the most common health conditions in schools between 2006 and 2016 [ 21 ]. However, the outcomes of school nurse-led practice regarding mental health [ 22 ] and pain have not been satisfactory [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, one survey identified a gap between the importance and performance for quality improvement and community/public health practice [ 27 ]. Best et al [ 21 ] mentioned noticeable increases in health services for asthma, type I diabetes, healthcare procedures, school nurse-led health counseling, and diabetes health counseling. There are more children and adolescents with chronic and special public health problems now than in the past.…”
Section: Discussionmentioning
confidence: 99%